Influence of 21st-Century Skills on Academic Resilience among University Students: A Quantitative Cross-Sectional Survey Study - Dr. Abdul Majid Khan Rana; Syed Ghazanfer Abbas (Policy Journal of Social Science Review, 2026)
The increasing complexity of higher education has intensified the need for students to acquire competencies that extend beyond traditional academic knowledge. Among these competencies, 21st-century skills including critical thinking, communication, collaboration, creativity, and digital literacy have become essential for enabling students to adapt to rapidly changing academic and professional environments. Simultaneously, academic resilience has emerged as an important psychological and educational construct that enables students to overcome academic setbacks, sustain motivation, and achieve long-term educational success. Despite the growing importance of both constructs, limited empirical evidence has comprehensively examined the influence of 21st-century skills on academic resilience within higher education settings. Therefore, this study investigated the influence of 21st-century skills on academic resilience among university students. A quantitative research approach employing a cross-sectional survey design was adopted. Data were collected from 400 undergraduate and postgraduate students selected through stratified random sampling from public and private universities. A structured five-point Likert-scale questionnaire measured five dimensions of 21st-century skills and four dimensions of academic resilience. Instrument validity was established through the Content Validity Index (CVI) and Exploratory Factor Analysis (EFA), while reliability was confirmed using Cronbach's alpha coefficients. Data were analyzed using descriptive statistics, Pearson correlation, independent-samples t-tests, one-way ANOVA, and multiple linear regressions. The findings indicated moderately high levels of both 21st-century skills and academic resilience among university students. Correlation analysis revealed a statistically significant positive relationship between the two constructs. Multiple regression analysis further demonstrated that 21st-century skills significantly predicted academic resilience, with critical thinking and digital literacy emerging as the strongest predictors. The proposed model explained a substantial proportion of variance in academic resilience. The study concludes that fostering 21st-century competencies significantly enhances students' academic resilience and their ability to cope with educational challenges. These findings provide empirical evidence supporting competency-based education and institutional strategies aimed at strengthening sustainable student success in higher education. Keywords: Academic resilience; 21st-century skills; higher education; critical thinking; digital literacy; university students; competency-based education.